(untitled) (Tanzania Medical Journal, 2007)
Background: CD4+ T-lymphocyte count is an indicator of immune status used as the eligibility criterion for initiation of antiretroviral therapy (ART) and for monitoring of immunological response to ART in HIV-infected patients in resource limited settings. Objective: To describe the immunological response to ART in HIV-1 infected ART naïve patients in relation to age, sex, baseline CD4+ T cell counts and generic ART regimens at Muhimbili Nation Hospital, in Dar es Salaam, Tanzania. Methods: Retrospective analysis of data from patients enrolled in the pilot ART program between July 2004 and August 2005. All were ART naïve and were mostly started on a fixed dose generic first line antiretroviral (ARV) drug combination of stavudine, lamivudine and nevirapine (triomune). Results: As of August 2005, 1435 patients were recruited for ART, of these 1285 (89.6%) were aged 13+ years. A total of 361 patients were included in the analysis. The mean (range) age was 39 years (13 – 69 years). Two hundred and fourty seven (68.4%) were females. The overall mean baseline CD4+ T cell count was 113 cells/μl; 105 (29.1%) patients had baseline CD4+ count < 50 cells/μl. Two hundred and ninety five (81.7%) received triomune. The overall mean CD4+ T cell count increase was 23 cells/μl. CD4+ T cell count increased more rapidly within the first three months of ART (mean of 27 cells/l per month), relatively slower thereafter and tended to plateau at 10 - 12 months. There were no significant differences in CD4+ T cell counts increase between the sexes, age groups and ART regimens. Conclusion: Initiation of ART resulted in overall good immunological responses even among patients who had CD4+ count of